1993
DOI: 10.1111/j.1741-6612.1993.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I Think He Might Have Hit Me Once’: Aggression Towards Caregivers in Dementia Care

Abstract: Little is known about aggression in caregiving relationships in the Australian context, although the topic has received considerable attention in recent overseas literature. This paper reports on a sample of 39 female primary caregivers recruited from the Brisbane metropolitan area and interviewed about a range of aggressive acts directed against them by dementing dependents, while they were providing care in the community. Results show that aggression against caregivers was reported in 89 per cent of cases. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Chrzescijanski and colleagues (2007) discuss the salience of this issue, noting that “managers of nursing home facilities, including some ‘dementia specific’ units, are often apprehensive about admitting people with challenging behaviours such as aggression” (p.272). Aggression towards caregivers in home environments can result in injury or trauma to the caregiver and may impact health outcomes for caregivers (Cahill & Shapiro, 2008). There is some evidence that home healthcare workers are four times more likely to experience assault if they have one or more patients with dementia (Galinsky et al, 2010), and this led to significantly shortened home care visits (impact on quality of care).…”
Section: Triggers To Violence and Issues Of Homecare And Healthcare Sermentioning
confidence: 99%
“…Chrzescijanski and colleagues (2007) discuss the salience of this issue, noting that “managers of nursing home facilities, including some ‘dementia specific’ units, are often apprehensive about admitting people with challenging behaviours such as aggression” (p.272). Aggression towards caregivers in home environments can result in injury or trauma to the caregiver and may impact health outcomes for caregivers (Cahill & Shapiro, 2008). There is some evidence that home healthcare workers are four times more likely to experience assault if they have one or more patients with dementia (Galinsky et al, 2010), and this led to significantly shortened home care visits (impact on quality of care).…”
Section: Triggers To Violence and Issues Of Homecare And Healthcare Sermentioning
confidence: 99%
“…At the Joint Congressional Hearings on Abuse of the Elderly (11 June 1980), it was reported that 10% of the nation's elderly are at risk within their families. If we include caregivers who are violent toward the elderly person, then we find that the unreported prevalence of violence can be as high as 17.4% (Paveza et al, 1992) or even as high as 26% (Cahill & Shapiro, 1993). Our research in Israel showed that 7% of respondents were aware of at least one case of elder abuse in their extended families (Neikrug & Ronen, 1993).…”
Section: The Knowledge Basementioning
confidence: 79%
“…One survey of paid staff reported that 89 percent had experienced aggression and 26 percent serious violence from those for whom they were caring (Cahill & Shapiro, 1993).…”
Section: What Staff Know About Elder Abuse In Dementia and The Effectmentioning
confidence: 99%